ANALISIS TERHADAP INTEGRASI VERTIKAL DITINJAU DARI PASAL 14 UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT (STUDI KASUS PUTUSAN KOMISI PENGAWAS PERSAINGAN USAHA NOMOR 13/KPPU-I/2019) - Vanessa Widjaja; Ariawan Gunadi (Jurnal Hukum Adigama, 2020)
In competition law, vertical integration is known as a business strategy. Vertical integration is the merger of two or more companies into one vertically related company. If vertical integration is carried out with the intention of inhibiting business competition and the economy at large, it is contrary to Article 14 of Law Number 5 of 1999 regarding the prohibition of monopolistic practices and unfair business competition. Therefore, every vertical integration requires further research using the rule of reason approach to see how and the extent to which this integration has an impact on business competition. However, the application of Article 14 vertical integration in Indonesia often creates pros and cons because people's perceptions often differ in the interpretation of the article.Therefore, this research looks for a common thread in order to achieve clarity regarding the application of Article 14 of Law Number 5 of 1999 to be applied in a case of vertical integration.